2012
DOI: 10.1002/hbm.22001
|View full text |Cite
|
Sign up to set email alerts
|

Phonological processing in first‐degree relatives of individuals with autism: An fMRI study

Abstract: Autism spectrum disorders (ASD) are complex neurodevelopmental disorders. Twin studies have provided heritability estimates as high as 90% for idiopathic ASD. Further evidence for the spectrum’s heritability is provided by the presence of the broad autism phenotype (BAP) in unaffected first-degree relatives. Language ability, specifically phonological processing, is proposed to be a core BAP trait. To date, however, no functional neuroimaging investigations of phonological processing in relatives of individual… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
23
0

Year Published

2013
2013
2019
2019

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 25 publications
(24 citation statements)
references
References 140 publications
(192 reference statements)
1
23
0
Order By: Relevance
“…Performance on all these tasks reflects the ability to maintain and manipulate auditory verbal or phonological information in short-term memory (e.g., 49). Such PWM deficits have been well documented in separate studies of children with reading disability (6, 50-52) or ASD (8, 11, 16). Our results show directly that a similar impairment of PWM is shared across poor readers and the age-, IQ-, and gender-matched children with ASD.…”
Section: Discussionmentioning
confidence: 85%
See 1 more Smart Citation
“…Performance on all these tasks reflects the ability to maintain and manipulate auditory verbal or phonological information in short-term memory (e.g., 49). Such PWM deficits have been well documented in separate studies of children with reading disability (6, 50-52) or ASD (8, 11, 16). Our results show directly that a similar impairment of PWM is shared across poor readers and the age-, IQ-, and gender-matched children with ASD.…”
Section: Discussionmentioning
confidence: 85%
“…Children with ASD, particularly those with broader language impairments, have also shown impaired phonological awareness and verbal short-term memory (8-11). Moreover, atypical verbal short-term memory was found among unaffected first-degree relatives, which indicates that impaired PWM is a prominent feature of the broader autism phenotype (16). …”
Section: Introductionmentioning
confidence: 99%
“…Children and adults who stutter also appear to have deficits in phonological working memory that may be independent of speech fluency (Anderson, Wagovich, & Hall, 2006;Byrd, McGill, & Usler, 2015;Hakim & Ratner, 2004). In autism, too, there is a pronounced impairment in phonological working memory (Kjelgaard & Tager-Flusberg, 2001), which appears to extend even to first-degree family members evincing the broad autism phenotype (Wilson et al, 2013).…”
mentioning
confidence: 99%
“…Consequently, Wilson and associates (2013) proposed that phonological processing differences in the brain appear to be a basic feature of the BAP. However, similar to Losh et al (2012), Wilson et al (2013) indicated that replication of their findings are necessary before any firm conclusions can be drawn.…”
Section: Phonological Processingmentioning
confidence: 75%
“…More recently, Wilson et al (2013) claimed that deficient phonological processing is "a core BAP trait" (p. 1447). They explored this supposition by using an fMRI to scan the brains of parents of children with ASD and control participants.…”
Section: Phonological Processingmentioning
confidence: 99%